Direito de informação no espaço virtual da internet: consolidação da cidadania - Carvalho, Ana Cristina Azevedo Pontes de (2013)
The innovations in the exercise of citizenship after the evolution of technology lead to reflections in the Law area, concerning information, liberty of expression and respect to private life. The use of cyberspace as a way to practice juridical acts was transformed by the creation and popularization of internet, which made possible the information process as no other way of communication could ever have done, due to the fact that it allowed people to inform, be informed and keep informed in an easier way. The modern conception of citizenship requires, not only solidarity to demand the rights for which the whole society is interested, but also covers the needing that all people have access to technology, otherwise it would make very difficult to exercise their rights. Inserted in the research area Citizenship Modeling the State , due to the needing of revision and consolidation of the concept of citizenship and the rising importance of the right to information, when internet plays a preponderant role on citizens life, the objectives of this thesis are: to analyze the role of the right to information on the cyberspace, reflecting about how it models the performance of the State and leads to the exercise of an active citizenship, modernizing democracy, and also to evaluate if this right is present in the construction of the rules for a civil regulation of the internet. The methodology comprehended a documental research, using both national and foreign literature, and also the current legal rules, the Law Project (and Substitutive) that intends to create the Civil Regulation of Internet and the case law, based on the literature of authors such as Alexy, Bucci, Castells, Dahl, Dworkin, Lévy and Pinsky. This thesis was divided in three chapters: the first one regards the transformations of society, related to the right to information; the second one studies the internet and its role on the exercise of citizenship; the third one analyzes how the creation of a civil regulation of internet in Brazil may promote the exercise of the right to information and consolidate citizenship. It was supported that the rules regarding the exercise of the right to information and applicable to the cyberspace of internet may consolidate citizenship, concluding that the Law Project 2.126/11 (and Substitutive) contains the main rules in order to cover these objectives, as an effective public policy related to the exercise of citizenship.